High-cholesterol diet in combination with hydroxypropyl-beta-cyclodextrin induces NASH-like disorders in the liver of rats - Saigo, Yasuka; Sasase, Tomohiko; Tohma, Marika; Uno, Kinuko; Shinozaki, Yuichi; Maekawa, Tatsuya; Sano, Ryuhei; Miyajima, Katsuhiro; Ohta, Takeshi (Physiological research, 2023)
Non-alcoholic fatty liver disease (NAFLD) is a general term for fatty liver disease not caused by viruses or alcohol. Fibrotic hepatitis, cirrhosis, and hepatocellular carcinoma can develop. The recent increase in NAFLD incidence worldwide has stimulated drug development efforts. However, there is still no approved treatment. This may be due in part to the fact that non-alcoholic steatohepatitis (NASH) pathogenesis is very complex, and its mechanisms are not well understood. Studies with animals are very important for understanding the pathogenesis. Due to the close association between the establishment of human NASH pathology and metabolic syndrome, several animal models have been reported, especially in the context of overnutrition. In this study, we investigated the induction of NASH-like pathology by enhancing cholesterol absorption through treatment with hydroxypropyl-beta-cyclodextrin (CDX). Female Sprague-Dawley rats were fed a normal diet with normal water (control group); a high-fat (60 kcal%), cholesterol (1.25 %), and cholic acid (0.5 %) diet with normal water (HFCC group); or HFCC diet with 2 % CDX water (HFCC+CDX group) for 16 weeks. Compared to the control group, the HFCC and HFCC+CDX groups showed increased blood levels of total cholesterol, aspartate aminotransferase, and alanine aminotransferase. At autopsy, parameters related to hepatic lipid synthesis, oxidative stress, inflammation, and fibrosis were elevated, suggesting the development of NAFLD/NASH. Elevated levels of endoplasmic reticulum stress-related genes were evident in the HFCC+CDX group. In the novel rat model, excessive cholesterol intake and accelerated absorption contributed to NAFLD/NASH pathogenesis.
Keywords: hypercholesterolemie; krysa rodu Rattus; Diet, High-Fat; nealkoholová steatóza jater; Humans; Female; Non-alcoholic Fatty Liver Disease; lidé; dieta s vysokým obsahem tuků; ženské pohlaví; modely nemocí na zvířatech; Rats; potkani Sprague-Dawley; cholesterol; 2-Hydroxypropyl-beta-cyclodextrin; Hyperlipidemias; játra; Animals; zvířata; Hypercholesterolemia; Liver; Rats, Sprague-Dawley; Disease Models, Animal; Cholesterol; hyperlipidemie; hydroxypropyl beta cyklodextrin